Application of Stad Type Cooperative Learning to Improve Learning Activities and Learning Outcomes - Yhasinta Agustyarini; Elmi Zuvia Zahro (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
The background of this study is the low student activity which has an impact on the learning outcomes of class V students in mathematics subjects. The purpose of this study is to improve learning activities and mathematics learning outcomes of class V MI Pancasila Gondang students through a cooperative learning model of the Student Teams Achievement (STAD) type. This study used a Classroom Action Research (PTK) design consisting of two cycles. Research data in the form of student learning activities is obtained through observation during learning, while student learning outcomes are obtained through tests at the end of each cycle. The results showed that student activity in cycle I was 56% then in cycle II increased to 85%, classical student learning outcomes in cycle I were 52% with an average student score of 66, then increased to 86% with an average student score of 76 in cycle II. It was concluded that using a Cooperative Learning Model type of Student Teams Achievement (STAD) can increase the activities and learning outcomes of class V students in the material building materials at MI Pancasila Gondang.